Tip110/SART3-Mediated Regulation of NF-κB Activity by Targeting IκBα Stability Through USP15 - Timani, Khalid Amine; Rezaei, Sahar; Whitmill, Amanda; Liu, Ying; He, Johnny J. (Frontiers in Oncology, 2022)
To date, there are a small number of nuclear-restricted proteins that have been reported to play a role in NF-κB signaling. However, the exact molecular mechanisms are not fully understood. Tip110 is a nuclear protein that has been implicated in multiple biological processes. In a previous study, we have shown that Tip110 interacts with oncogenic ubiquitin specific peptidase 15 (USP15) and that ectopic expression of Tip110 leads to re-distribution of USP15 from the cytoplasm to the nucleus. USP15 is known to regulate NF-κB activity through several mechanisms including modulation of IκBα ubiquitination. These findings prompted us to investigate the role of Tip110 in the NF-κB signaling pathway. We showed that Tip110 regulates NF-κB activity. The expression of Tip110 potentiated TNF-α-induced NF-κB activity and deletion of the nuclear localization domain in Tip110 abrogated this potentiation activity. We then demonstrated that Tip110 altered IκBα phosphorylation and stability in the presence of TNF-α. Moreover, we found that Tip110 and USP15 opposingly regulated NF-κB activity by targeting IκBα protein stability. We further showed that Tip110 altered the expression of NF-κB-dependent proinflammatory cytokines. Lastly, by using whole-transcriptome analysis of Tip110 knockout mouse embryonic stem cells, we found several NF-κB and NF-κB-related pathways were dysregulated. Taken together, these findings add to the nuclear regulation of NF-κB activity by Tip110 through IκBα stabilization and provide new evidence to support the role of Tip110 in controlling cellular processes such as cancers that involve proinflammatory responses.